2021
DOI: 10.1007/s00125-021-05517-0
|View full text |Cite
|
Sign up to set email alerts
|

ZBED6 counteracts high-fat diet-induced glucose intolerance by maintaining beta cell area and reducing excess mitochondrial activation

Abstract: Aims/hypothesis ZBED6 (zinc finger, BED-type containing 6) is known to regulate muscle mass by suppression of Igf2 gene transcription. In insulin-producing cell lines, ZBED6 maintains proliferative capacity at the expense of differentiation and beta cell function. The aim was to study the impact of Zbed6 knockout on beta cell function and glucose tolerance in C57BL/6 mice. Methods Beta cell area and proliferation were determined in Zbed6 knockout mice usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In CNS, Egr1 mRNA expression level was significantly decreased in cognitive dysfunction model of T2DM mice [35]. Zbed6, zinc finger BED domain-containing protein 6, established a role in regulating IGF2 mRNA expression and insulin production, maintaining beta cell area, and reducing excess mitochondrial activation [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In CNS, Egr1 mRNA expression level was significantly decreased in cognitive dysfunction model of T2DM mice [35]. Zbed6, zinc finger BED domain-containing protein 6, established a role in regulating IGF2 mRNA expression and insulin production, maintaining beta cell area, and reducing excess mitochondrial activation [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) sequencing using murine C2C12 cells indeed demonstrated that ZBED6 may regulate additional 1200 ZBED6 binding sites other than IGF2 [ 4 ]. ZBED6 regulates beta cell area and excess mitochondrial activation by controlling the cell cycle gene PTTG1 and the mitochondrial regulator PPAR-γ related coactivator 1 protein (PRC) in mice, which occurred independently from ZBED6 effects on IGF2 gene expression [ 13 ]. However, the functional role of ZBED6 in pig besides its important role for regulating IGF2 expression is still poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…While our findings support the notion that NOX4 is harmful in stressed human beta-cells, it is also possible that short-term NOX 4 activation mediates beneficial effects. Mitochondrial overactivation and metabolic maladaptation have recently been suggested to be an early response to chronic glucose stress in beta cells [ 27 ], and protecting mitochondria from this nutrient overload may preserve normal beta-cell function [ 28 ]. NOX4 inhibition might modulate the mitochondrial activity of beta-cells enough for them to overcome the stress from a diabetic milieu.…”
Section: Discussionmentioning
confidence: 99%